MANAJEMEN PROGRAM ADIWIYATA DALAM MEMBENTUK BUDAYA SEKOLAH PEDULI LINGKUNGAN - Esih Rusmiati; Helmawati Helmawati (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
The increasing complexity of environmental problems requires education to play a strategic role in fostering students’ ecological awareness through sustainable programs. The Adiwiyata Program, as a national policy in Indonesia, aims to develop environmentally responsible and cultured schools; however, its implementation often reveals a gap between administrative achievements and actual behavioral change. This study aims to analyze the management of the Adiwiyata Program based on the planning, organizing, actuating, and controlling (POAC) cycle in fostering an environmentally conscious school culture. A qualitative approach with a case study design was employed in two elementary schools in Bandung. Data were collected through observations, in-depth interviews, and document analysis, and analyzed using an interactive model. The findings indicate that program effectiveness is not determined by the intensity of activities but by the integration quality of managerial functions. In the planning dimension, administrative orientation tends to dominate over contextual strategies. Organizing shows indications of pseudo-participation, while implementation risks becoming routine activities without meaningful value internalization. In the controlling stage, evaluation practices tend to reinforce administrative compliance rather than cultural transformation. This study concludes that the effectiveness of the Adiwiyata Program depends on shifting from compliance-based management to culture-based management, emphasizing sustainable ecological awareness. ABSTRAK Permasalahan lingkungan hidup yang semakin kompleks menuntut peran strategis pendidikan dalam membentuk kesadaran ekologis peserta didik melalui program yang berkelanjutan. Program Adiwiyata sebagai kebijakan nasional bertujuan mewujudkan sekolah peduli dan berbudaya lingkungan, namun implementasinya masih menghadapi kesenjangan antara capaian administratif dan perubahan perilaku nyata. Penelitian ini bertujuan menganalisis secara mendalam manajemen Program Adiwiyata berbasis siklus planning, organizing, actuating, dan controlling dalam membentuk budaya sekolah peduli lingkungan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus pada dua sekolah dasar di Kota Bandung. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan model interaktif. Hasil penelitian menunjukkan bahwa keberhasilan program tidak ditentukan oleh intensitas kegiatan, tetapi oleh kualitas integrasi fungsi manajemen. Pada dimensi perencanaan ditemukan kecenderungan dominasi administratif dibandingkan pendekatan kontekstual. Pengorganisasian masih menunjukkan gejala partisipasi semu, sementara pelaksanaan berpotensi terjebak dalam rutinitas tanpa internalisasi nilai. Pada tahap pengawasan, evaluasi cenderung menghasilkan kepatuhan administratif dibandingkan transformasi budaya. Simpulan penelitian menegaskan bahwa efektivitas Program Adiwiyata hanya dapat dicapai melalui pergeseran dari compliance-based management menuju culture-based management yang berorientasi pada pembentukan kesadaran ekologis secara berkelanjutan.